(untitled) (Research, Society and Development, 2022)
This work aimed to analyze the micropropagation technique in two pitaya species under different concentrations of growth regulators and the effect of different substrates on the acclimatization of their seedlings. The research took place at the Plant Biotechnology Laboratory – BIOVEG – belonging to the Federal University of Alagoas – CECA/UFAL. Seeds of mature fruits of H. undatus and H. megalanthus from commercial plantations in the states of Pernambuco and Ceará, respectively, were used. Two pitaya species (H. undatus and H. megalanthus) and four concentrations of IBA, four concentrations of 6-benzylaminopurine plus the control (without IBA or BAP) were used. A rooting experiment with the same culture media used in the multiplication experiment, but using microcladodes with only the base part removed. The results showed that cytokinin BAP considerably stimulated the production of new shoots in both pitaya species when compared to the control. The species H. megalanthus presented number of sprouts and roots than the species H. undatus. The substrates Bioplant and cajá seed fiber presented results for length and number of roots, as well as for fresh and dry mass superior to vermiculite for the two studied species, being indicated for the production of pitaya seedlings. The purple pitaya variety was the one that always showed the best responses in shoots and roots, both in vitro and extra vitro.